2011
DOI: 10.1097/acm.0b013e318217e83b
|View full text |Cite
|
Sign up to set email alerts
|

Stories From Early-Career Women Physicians Who Have Left Academic Medicine: A Qualitative Study at a Single Institution

Abstract: Participants report a disconnection between their own priorities and those of the dominant culture in academic medicine. Efforts to retain women faculty in academic medicine may include exploring the aspects of an academic career that they value most and providing support and recognition accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
133
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 24 publications
5
133
3
5
Order By: Relevance
“…1,2 Within academic settings, their rate of promotion and appointment to leadership roles lags significantly behind their male counterparts', and their attrition rate exceeds that of men. [1][2][3] Cited reasons include lack of perceived positive role models and insufficient support, mentorship and preparation. 3,4 Women have more difficulty identifying potential mentors, despite seeking them more often than men do.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Within academic settings, their rate of promotion and appointment to leadership roles lags significantly behind their male counterparts', and their attrition rate exceeds that of men. [1][2][3] Cited reasons include lack of perceived positive role models and insufficient support, mentorship and preparation. 3,4 Women have more difficulty identifying potential mentors, despite seeking them more often than men do.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Cited reasons include lack of perceived positive role models and insufficient support, mentorship and preparation. 3,4 Women have more difficulty identifying potential mentors, despite seeking them more often than men do. 4 Women also report satisfying mentoring relationships less frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Les mentors femmes ou issus des minorités pourraient mieux comprendre les problèmes rencontrés par ces groupes et pourraient être encore plus difficiles à identifier. [10][11][12] Des programmes officiels de mentorat ciblant ces populations pourraient améliorer l'accès au mentorat. 5 Enfin, les médecins s'orientant vers la médecine clinique ou l'éducation ont une moindre probabilité d'avoir un mentor que ceux s'orientant principalement vers la recherche.…”
Section: Mentorat En Anesthésie: Nous En Savons Si Peu…unclassified
“…Female or minority mentors may have increased understanding of the issues faced by these groups and may be even more difficult to identify. [10][11][12] Formal mentorship programs targeting these populations may improve access to mentorship. 5 Finally, physicians whose focus is clinical medicine or education are less likely to be mentored than those who are primarily research-focused.…”
mentioning
confidence: 99%
“…A recent qualitative study of women who left academic institutions confirmed that the difficulty with work-life balance was a factor in the decision to leave [2].…”
mentioning
confidence: 99%